2020
DOI: 10.1364/boe.379518
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic interferometric immunosensor based on polydimethilsiloxane (PDMS) and bioactive lipids

Abstract: We demonstrate a novel and simple means to fabricate optical fiber immunosensors based on Fabry-Perot (F-P) interferometers using polydimethylsiloxane (PDMS) as support for bioactive lipids. The sensors are fabricated following a straightforward dip-coating method producing PDMS end-capped devices. A biosensing platform is realized by subsequent functionalization of the PDMS cap with a previously characterized bioactive lipid antigen cocktail from Mycobacterium fortuitum, used as a surrogate source of antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, regenerating an immunosensor relies on detaching antigens from the antibodies on the fiber surface, a process that can damage the antibodies and hinder repeated usage. Therefore, while there is already some research regarding sensor regeneration and reusability using acid solutions [ 13 , 127 , 144 , 145 ], these remain a challenge for the future. In addition, the ability for detection of various parameters within a single optical fiber device [ 85 , 146 ] is another challenge to overcome in the promising future of biosensing.…”
Section: Final Remarks and Future Outlookmentioning
confidence: 99%
“…However, regenerating an immunosensor relies on detaching antigens from the antibodies on the fiber surface, a process that can damage the antibodies and hinder repeated usage. Therefore, while there is already some research regarding sensor regeneration and reusability using acid solutions [ 13 , 127 , 144 , 145 ], these remain a challenge for the future. In addition, the ability for detection of various parameters within a single optical fiber device [ 85 , 146 ] is another challenge to overcome in the promising future of biosensing.…”
Section: Final Remarks and Future Outlookmentioning
confidence: 99%
“…An optical fiber was originally developed to guide light waves along the core, which is surrounded by a cladding layer through the total internal reflection at the interface with negligible loss. Over the last few decades, optical fibers have been extensively investigated for biosensing applications, with the intrinsic advantages including flexibility, low-cost, small size, and biocompatibility [ 39 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. To be developed as a biosensor, the structure of optical fiber has modified to maximize the interaction of light with target analytes and increase the sensitivity [ 66 ].…”
Section: Fabry-perot Interferometer (Fpi)-based Biosensorsmentioning
confidence: 99%
“…They were able to detect DTT down to 50 μM. Cano-Velazquez et al also reported a polydimethylsiloxane (PDMS)-coated optical fiber FPI as shown in Figure 11 b [ 72 ]. The PDMS has been widely used to fabricate optical and microfluidic devices by virtue of the transparency, ease-of-use, and biocompatibility.…”
Section: Fabry-perot Interferometer (Fpi)-based Biosensorsmentioning
confidence: 99%
“…They demonstrate a fluorometric optical sensor system for the sensitive, real time measurement of volatile organic compounds (VOCs) as biomarkers of urinary bladder cancer. In Cano-Velázquez et al [15], functionalized polydimethylsiloxane enables label-free, real-time immunosensing of antigens for tuberculosis diagnosis. This work speaks to the more general promise of simple optical methods to enable novel analytical tools.…”
Section: Biosensorsmentioning
confidence: 99%